Using a health system learning community strategy to address cancer disparities. Issue 4 (18th September 2018) - Myers, Ronald E.; DiCarlo, Melissa; Romney, Martha; Fleisher, Linda; Sifri, Randa; Soleiman, Joy; Lambert, Emily; Rosenthal, Michael
Abstract: Accountable care organizations and health systems have the potential to increase patient engagement in medical care, improve population health outcomes, and reduce costs. Characteristics of highly integrated learning health care systems that seek to achieve these goals have been described in the literature. However, there have been few reports on how health systems, especially those that are loosely integrated, can develop the infrastructure needed to support achievement of these goals. In this report, we describe a learning community strategy that involved forming a coordinating team, a steering committee, and patient and stakeholder advisory committees to address cancer screening and disparities in 2 health systems in southeastern Pennsylvania—Jefferson Health and the Lehigh Valley Health Network. This project engaged diverse patients, health care providers, health system leaders, public and private payers, and other stakeholders in identifying and adapting evidence‐based methods to increase colorectal and lung cancer screening in primary care. Here, we describe components of a health system learning community. In addition, we describe activities in which different components of the learning community were engaged. Finally, we explore prospects for using this type of approach to catalyze the development of learning health care systems.